Monetary Stabilization and the Informational Value of Monetary Aggregates - Siegel, Jeremy J. (Journal of Political Economy, 1982)
A simple stochastic model is developed which demonstrates that information on the nominal value of money conveys sufficient information about the disturbance to currency and deposit demand so that monetary prices, such as adjusting the level of bank reserves, have no impact on the dispersion of price level forecast errors. However, if information on monetary aggregates is obtained only with a lag, then reserve requirements can reduce the disturbances to the demand for high-powered money and hence prices. Such a reserve ratio depends critically on the variance-covariance matrix of shocks to the monetary demands.